2013
DOI: 10.4303/jdar/235669
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Kinase Mζ (PKMζ) in the Mesolimbic System Alters Cocaine Sensitization in Rats

Abstract: Chronic cocaine use produces long-lasting changes in reward circuits that may underlie the transition from casual to compulsive patterns of drug use. Although strong neuroadaptations within the mesocorticolimbic system are known to occur, the specific role of these drug-induced plasticities on sensitization remains to be elucidated. Here we investigate whether PKMζ, a protein involved in maintaining long-term potentiation (LTP), plays a role in these cocaine-induced changes in synaptic strengthening. We perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
2
11
1
Order By: Relevance
“…We note that Volk et al had reported ZIP induces decreases in both tetanized and untetanized pathways in slices ( Volk et al, 2013 ). These results conflict with evidence from a large number of studies showing exclusive actions of ZIP in tetanized or facilitated pathways and not in baseline pathways, including seven studies in brain slices of fEPSPs ( Ling et al, 2002 ; Serrano et al, 2005 ; Sajikumar et al, 2005 ; Navakkode et al, 2010 ; Lin et al, 2012 ; Panaccione et al, 2013 ; Chen et al, 2015 ), four studies of EPSCs ( Li et al, 2010 ; Yao et al, 2013 ; Velez-Hernandez et al, 2013 ; Li et al, 2014 ), two studies in model systems ( Cai et al, 2011 ; Balaban et al, 2015 ), and four studies in vivo of fEPSPs ( Pastalkova et al, 2006 ; Madronal et al, 2010 ; Dong et al, 2015 ) and evoked responses ( Cooke and Bear, 2010 ), as well as evidence of stable basal properties of hippocampal neurons following ZIP injections recorded in vivo ( Barry et al, 2012 ). DOI: http://dx.doi.org/10.7554/eLife.14846.004
10.7554/eLife.14846.005 Figure 1—figure supplement 2.
…”
Section: Resultscontrasting
confidence: 89%
“…We note that Volk et al had reported ZIP induces decreases in both tetanized and untetanized pathways in slices ( Volk et al, 2013 ). These results conflict with evidence from a large number of studies showing exclusive actions of ZIP in tetanized or facilitated pathways and not in baseline pathways, including seven studies in brain slices of fEPSPs ( Ling et al, 2002 ; Serrano et al, 2005 ; Sajikumar et al, 2005 ; Navakkode et al, 2010 ; Lin et al, 2012 ; Panaccione et al, 2013 ; Chen et al, 2015 ), four studies of EPSCs ( Li et al, 2010 ; Yao et al, 2013 ; Velez-Hernandez et al, 2013 ; Li et al, 2014 ), two studies in model systems ( Cai et al, 2011 ; Balaban et al, 2015 ), and four studies in vivo of fEPSPs ( Pastalkova et al, 2006 ; Madronal et al, 2010 ; Dong et al, 2015 ) and evoked responses ( Cooke and Bear, 2010 ), as well as evidence of stable basal properties of hippocampal neurons following ZIP injections recorded in vivo ( Barry et al, 2012 ). DOI: http://dx.doi.org/10.7554/eLife.14846.004
10.7554/eLife.14846.005 Figure 1—figure supplement 2.
…”
Section: Resultscontrasting
confidence: 89%
“…ζ -pseudosubstrate inhibitory peptide (ZIP), a selective inhibitor of PKM ζ , can reverse LTP maintenance and block L-LTP induction [ 14 , 15 ]. Furthermore, ZIP can also reverse a variety of memory types, such as spatial information, fear, addiction, and conditioned taste aversion (CTA) memory [ 15 19 ]. Several studies have reported that PKM ζ -related pain memory can be erased in the spinal cord and the brain [ 9 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term changes in the VTA are induced by a single and multiple cocaine injections [40,41]. In addition, LTP, as the persistent increase in AMPA/NMDA ratio on VTA DA cells, is critical for the maintenance of cocaine sensitization [63]. These changes in synaptic plasticity in the VTA have been implicated in the development of drug addiction and cocaine sensitization [5,54,64,65].…”
Section: Discussionmentioning
confidence: 99%